Doses de potássio na cultura do crambe - Santos, Vanessa dos; Andrade, Vinicius Gabriel; Fim, Wesley Luis Antonio; Gaion, Lucas Aparecido (Revista de Ciências Agroveterinárias, 2024)
Crambe (Crambe abyssinica), belonging to the Brassicaceae family, stands out for its agricultural potential. However, little is known about the crop's potassium requirements. Therefore, the objective of the present work was to evaluate the effect of doses of potassium (K2O) on the development and production of crambe plants. Thus, an experiment was installed in a greenhouse in the municipality of Marília-SP in 2023, to verify the responses to different doses of K2O. A completely randomized design was used, with four treatments, consisting of doses of K2O (0; 50; 100 and 200 kg ha-1 K2O), and five replications, totaling 20 experimental units. The experimental units consisted of 3.5 L pots filled with ravine soil. While the dose of 50 kg ha-1 K2O was all applied at the time of sowing, the doses of 100 and 200 kg ha-1 K2O were divided between planting fertilization (50 kg ha-1) and the remainder in coverage (30 days after sowing) to minimize soil salinization. Aspire fertilizer was used as a source of K2O. Furthermore, when sowing, the formula NPK 10-46-00 + 9% S was used, applying, respectively, 22, 100 and 19.8 kg ha-1 of N, P2O5 and S. At 109 days after sowing (DAS), the green mass of leaves and the K content in the leaves were evaluated and at 122 DAS, plants at maturity, the weight and yield were evaluated. The use of different doses of K2O did not cause a significant effect on the growth parameters of crambe plants. On the other hand, productivity data showed an increasing linear response in response to K2O doses. These results demonstrate that despite their rusticity, crambe plants are capable of responding to K2O fertilization.